Dynamic Modeling Process of Neuro Fuzzy System to Control the Inverted Pendulum System - Tharwat O. S. Hanafy; Mohamed K Metwally (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The analysis and control of complex plants often requires the principles of qualitative process models since quantitative, namely analytical process models are not available. Qualitative modeling is one promising approach to the solution of difficult tasks automation if qualitative process models are not available. This contribution presents a new concept of qualitative dynamic process modeling using so called Dynamic Adaptive Neuro fuzzy Systems. This yields the framework of a new systems theory the essentials of which are given in further section of the paper. First, an identification method is presented, using a combination of linguistic knowledge.